Sensory cue interactions in person perception : insights from ageing and developmental prosopagnosia - Maguinness, Corrina (Trinity College (Dublin, Ireland). School of Psychology, 2015)
A large body of behavioural and neuropsychological research, using static images of faces, has informed our understanding of the mechanisms underlying identity processing. Indeed, pioneering studies revealed dedicated modules for the processing of facial form in the human brain. Yet interactions with people in the real world are accompanied by a greater variety of sensory information beyond visual images, for example, people move and speak and are thus highly dynamic, multisensory stimuli. While these additional cues (e.g. facial motion, body motion and the voice) have received attention from researchers in the field, they have largely been studied in isolation, possibly driven by assumptions that each identity cue was processed independently.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin